Brief History of Science Translation in China - Jianzhong, Xu (Meta, 2005)
AbstractScience translation is a new branch of learning in China, but its practice can be traced back to about 200 BC. It includes all the practical fields but literary translation. It is the translation activity that mainly conveys science information, especially a thought activity and extra-language activity of the translator’s using target language to express the science information of source language so as to pursue the similar information. This paper briefly examines its history chronologically, and explores its gradual movement from practice to theory, from written translation to oral interpretation, from general theory to discipline studies. The history of science translation is composed of human translation and machine translation, but this paper only deals with the former.